Kepemimpinan Gembala Menurut 2 Timotius 2 dan Relevansinya di Era Melineal - Peter J.R. Wowor (Sekolah Tinggi Teologi Berita Hidup, 2021)
Jesus Christ had given the leadeeship baton to Paul as an evangelist, then Paul also continue the same thing, namely giving the baton to his spiritualson named Timothy. Then also advising Timothy in 2 Timothy 2 to give the baton to a capable person, to teach, and so on until our present era, namelytehe melineal era. This Leadership belongs to God so that humans as leadership actors are not accountable to humans but they must be accountable to God who gave them responsibility. In 2 Timothy 2, Paul advised Tiimothy to be ready to replace his leadershipand he also had to prepare a successor from his leadership. Based on the description in 2 Timothy 2 there are 3 things we can find abaout leadership, namely the first is strong leadership, the second is regenerative leadership and the third is leadership wirh character. Leadership that is strong, regenerative and with character must inspire shepherds in the melineal era in carryingout the leadership entrusted to them.Yesus Kristus telah memberikan tongkat estafet kepemimpinan kepada Paulus sebagai pemberita Injil, kemudian Paulus juga melanjutkan hal yang sama yaitu memberikan tongkat estafet tersebut juga kepada anak rohaninya yang bernama Timotius, kemudian juga menasihat Timotius dalam kitab 2 Timotius 2 untuk memberikan tongkat estafet itu kepada orang yang cakap untuk mengajar, demikian seterusnya sampai pada era kita sekarang yaitu era milenial. Kepemimpinan ini adalah milik Allah sehingga manusia sebagai pelaku kepemimpinan bukan bertanggung-jawab kepada manusia melainkan mereka harus bertanggung jawab kepada Allah yang memberi mereka tanggung jawab. Dalam 2 Timotius 2, Paulus menasihati Timotius agar siap menggantikan kepemimpinannya serta dia juga harus mempersiapkan penerus dari kepemimpinannya. Berdasarkan uraian dalam 2 Timotius ada 3 hal yang dapat ditemui tentang kepemimpinan yaitu: yang pertama adalah kepemimpinan yang kuat, yang kedua adalah kepemimpinan yang regeneratif dan yang ketiga adalah kepemimpinan yang berkarakter. Kepemimpinan yang kuat, regeneratif dan yang berkarakter harus menjiwa para gembala di era milenial dalam melaksanakan kepemimpinan yang dipercayakan kepadanya.